Quality Of Population Administration Services Improving Public Services Based On Kepmen No. 25 Of 2004 (Study Of Lubuk Pakam City III) - Faisal Dasyah (Institute Of computer Science (IOCS), 2021)
This study aims to determine the quality of population administration services in terms of issuing Identity Cards in Lubuk Pakam III Village based on the Decree of the Minister of Administrative Reform Number Kep/25/M.PAN/2/2004 dated February 24, 2004 concerning General Guidelines for Compiling the Unit Community Satisfaction Index. Government agency services, and the factors that influence the quality of service for issuing Identity Cards in Lubtik Pakam III Village, Lubuk Pakam District, based on Kepmenpan Number 25 of 2004. This study uses a qualitative descriptive method with a case study approach with inductive data analysis techniques using a single table. then look for the average service quality variable. Collecting data using library research and field research. Based on the results of data analysis, it is known that. the quality of population administration services in terms of the issuance of Identity Cards in Lubuk Pakam III Village based on the Decree of the Minister of Administrative Reform No. Kep/25/M.PAN/2/2004 dated February 24, 2004 concerning General Guidelines for Compiling the Community Satisfaction Index for Service Units of Government Agencies. poor category. where from the 14 elements of service, there are 7 (seven) elements of service that are not good and 7 (seven) elements of service that are included in the good category, namely courtesy and friendliness of officers, certainty of service schedules, environmental comfort. Based on the results of the research and the conclusions mentioned above, the authors contribute suggestions to improve aspects of knowledge where the real aspect is one of the requirements for improving the quality of human resources so that they can create human resources who are able to think ahead.